TEORI PEROLEHAN DAN PERKEMBANGAN BAHASA UNTUK JURUSAN PENDIDIKAN BAHASA ARAB - Hidayat, Yayat (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
Intelligence and learners’ language development is inseparable from the role of language education, both from elementary to advanced level, from formal to informal education. Learning design is closely related to daily activities of learners in listening, communicating, writing and also reading. The most important thing in the concept of language learning is how to teach the language through direct experience that stresses in the process of habituation and the process of ongoing lesson.Keywords: The role of language education, learning design, experiential learning